FPGA implementation of RS codec with interleaver in DVB-T using VHDL - Kamar, Sara; Fouda, Abdelmoniem; Zekry, Abdelhalim; Elmahdy, Abdelmoniem (International Journal of Engineering and Technology, 2017)
Digital television (DTV) provides a huge amount of information to many users at low cost. Recently, it can be packaged and fully integrated into completely digital transmission networks. Reed-Solomon code (RS) is one type of error correcting codes that can be used to enhance the performance of DTV. Interleaving/deinterleaving process enhances the performance of channel errors by spreading out random errors, very high-speed hardware description language (VHDL) is used in electronic design automation. It can be used as a general-purpose parallel programming language.This paper presents VHDL program for Reed-Solomoncodec (204, 188) and convolutional interleaver/deinterleaver, used in Digital Video Broadcasting-terrestrial system (DVB-T), according to ETSI EN 300 744 V1.5.1 standard. The VHDL programs are implemented on Xilinx 12.3 ISE and then simulated and tested via ISE simulator then the code is synthesized on FPGA device the results are compared with IP core for Xilinx 12.3 ISE, which gives the same results.